Joanne M.A. Murphy and Jerolyn E. Morrison (eds) Kleronomia: Legacy and Inheritance. Studies on the Aegean Bronze Age in Honor of Jeffrey S. Soles. - Alvarez, Laura E. (Journal of Greek Archaeology, 2023)
pp. 310. INSTAP: Academic Press, 2022. ISBN 978-1931534284, 64.95 (hardcover).